Association of the HLA‐G 3′UTR polymorphisms with colorectal cancer in Italy: a first insight. (21st December 2015) - Garziera, M.; Catamo, E.; Crovella, S.; Montico, M.; Cecchin, E.; Lonardi, S.; Mini, E.; Nobili, S.; Romanato, L.; Toffoli, G.
Summary: This study aimed to explore functional and regulatory polymorphisms and haplotypes at the HLA‐G 3′UTR region in colorectal cancer development. The presence of nonpolymorphic variants was also evaluated. Three‐hundred and eight patients with colorectal cancer and 294 healthy controls were analysed at the germinal level. We found an association with increased risk of colorectal cancer for +2960 14‐bp INDEL, +3196 C>G SNPs and UTR‐2 haplotype, and a 'protective' role for +3003 T>C, +3010 C>G polymorphisms and UTR‐4 haplotype. We detected in 3 distinct patients, a novel nucleotide change (+3037 C>A) and 2 already described rare variants, +3032 G/C (EUR MAF = 0.1%) and +3092 G/T (EUR MAF = 0%). This is the first study showing associations between different polymorphisms in the HLA‐G 3′UTR and colorectal cancer susceptibility.